2017
DOI: 10.1016/j.athoracsur.2017.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms Are More Useful Than Echocardiography in Patient Selection for Pulmonary Endarterectomy

Abstract: Patients with mild CTEPH can benefit from PEA, but may not be detected by TTE. Symptomatic patients with functional limitation and persistent mismatched perfusion defects on VQ scan should undergo further investigations with pulmonary angiogram and RHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
(26 reference statements)
2
14
0
Order By: Relevance
“…In CTEPH, as in pulmonary arterial hypertension, ZHAI et al [35] demonstrated that the ventilatory efficiency is impaired and highlighted that for CTEPH there was no correlation to the functional classes; however, no CTED patients were included in their report. DONAHOE et al [7] demonstrated increased ventilatory equivalents for carbon dioxide at anaerobic threshold and peak exercise similar to the results for our patients, but no post-operative data exist. One case report of CTED described improvements in right ventricular performance and ventilatory efficiency following PEA, but no exercise RHC data were mentioned [36].…”
Section: Cardiopulmonary Exercise Testssupporting
confidence: 88%
See 3 more Smart Citations
“…In CTEPH, as in pulmonary arterial hypertension, ZHAI et al [35] demonstrated that the ventilatory efficiency is impaired and highlighted that for CTEPH there was no correlation to the functional classes; however, no CTED patients were included in their report. DONAHOE et al [7] demonstrated increased ventilatory equivalents for carbon dioxide at anaerobic threshold and peak exercise similar to the results for our patients, but no post-operative data exist. One case report of CTED described improvements in right ventricular performance and ventilatory efficiency following PEA, but no exercise RHC data were mentioned [36].…”
Section: Cardiopulmonary Exercise Testssupporting
confidence: 88%
“…These patients have symptoms like dyspnoea upon exertion or fatigue that hamper their daily activities and diminish their quality of life. CTED patients show the same exercise limitations and symptoms as World Health Organization (WHO) Functional Class II or III CTEPH patients as described by DONAHOE et al [7]. These symptoms are in line with an inadequate response in pulmonary haemodynamics during exercise [8][9][10].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In the aforementioned meta-analysis, 3 of the 14 studies which confirmed CTEPH by RHC, 4,7,8,[11][12][13][14][15][16]18,19,21,23,26 9 studies had screened all included patients with echo, 8,11,12,[14][15][16]18,21,26 whereas echo was only performed in patients reporting dyspnea in 4 other studies. 4,7,13,23 Overall, systematic screening did not increase CTEPH detection rate, as the incidence of CTEPH was the same whether all patients were screened post-PE or only symptomatic patients were investigated.…”
Section: Key Evidencementioning
confidence: 99%